COVID-19 containment measures of the Government of Kenya: Impact on food security and farmers’ socio-economic life - Karen Mwende Kinuthia; Emy Susanti (Faculty of Social and Political Science, Universitas Airlangga, 2021)
Agriculture is the backbone of Kenya’s economy. The majority of the population earn their living through agricultural activities, large-scale and small-scale farming. This study seeks to reveal how the government’s COVID-19 containment measures have affected the agricultural sector and their impact on farmers’ lifestyle changes. This study employed qualitative research methods, with primary and secondary data sources, and conducted in-depth interviews with 12 farmers and agricultural producers of Gatanga Sub-county in Murang’a County, Kenya. This study shows that the farmers experienced economic shocks owing to the fluctuated farm gate prices and projected resource scarcity. In contrast, their lifestyle changed due to income decrease and adjustment of commodity priorities and socio-demographic factors. The severity of COVID-19 impact on agriculture in the Gatanga Sub-County has been doubled by crop destruction, planting delays, and heavy rains that influence scarcity of food commodities. The study recommends other research to evaluate alternative solutions to supply the county’s food outputs other than those already in co-operatives, like tea, coffee, milk, and avocados. Moreover, perhaps the question for other future researchers should now be directed toward the vulnerable families’ daily consumptions to fulfill their food needs.